Analisis Gaya Bahasa Dalam Pidato Nadiem Makarim Sebagai Rekomendasi Materi Ajar Pada Pembelajaran Teks Pidato Persuasif Sekolah Menengah Pertama - Aulia, Lulu; Pratiwi, Wienike Dinar; Nurhasanah, Een (Jurnal Ilmiah Wahana Pendidikan, 2024)
The phenomenon of fluency in speaking both among the public and students has an important role in building interaction and society so that it can work well with the other person speaking. The aim of the research is to find out the transcribed utterances that contain figurative language based on Gorys Keraf's theory in several speeches by Nadiem Makarim as Minister of Education, Culture, Research and Technology. The benefits of this research can increase vocabulary in speaking, especially in speeches. This study uses a descriptive qualitative method with a phenomenological approach. The data source used is the transcript of Nadiem Makarimm's speech as Minister of Education and Culture. The data collection methods in this study were (1) observing video speeches and reading the results of speech transcripts, (2) marking things that show Gorys Keraf's style of language.The results of the research show that the language style used shows all forms of language style in theory and is dominated by metaphorical language style. The results of this study become recommendations for teaching materials in learning Persuasive Speech Text in Junior High Schools. Teaching materials are packaged with computer-based multimedia and interactive videos.